Optimalisasi Pemeliharaan Aset Rumah Sakit: Pendekatan Preventif dan Teknologi Terbaru - Rasdian; Andika Mayansara (STIKES Garuda Putih, 2025)
Hospital asset and facility management in Indonesia post-COVID-19 faces increasingly complex challenges, particularly regarding the limitations of physical facilities, medical equipment, and human resource management. The pandemic has exacerbated these conditions, forcing hospitals to adapt quickly and implement technology-based solutions to maintain healthcare service quality. This study aims to explore the challenges and opportunities in hospital asset and facility management in Indonesia post-pandemic. The method used is a literature review through searches in databases such as Google Scholar, PubMed, and Scopus. A total of 45 articles were initially obtained, then filtered using inclusion criteria of being published within the last 10 years, addressing hospital asset and facility management, and applying valid methodologies. After the selection process, 20 articles were analyzed thematically to identify trends, challenges, and opportunities. The results show that the use of technology, such as digital management systems, telemedicine, and cloud-based asset management, provides significant opportunities to enhance efficiency, reduce waste, and improve service quality. Furthermore, the adoption of green technology, including renewable energy and efficient waste management, can reduce operational costs and strengthen long-term sustainability. Government policies that support digital transformation and sustainability are also found to play a vital role in accelerating hospital adaptation. In conclusion, while substantial challenges remain, hospitals have significant opportunities to leverage digital and green technologies to improve asset and facility management. Therefore, government support becomes a key factor in enhancing efficiency and service quality in the future.